Objective-Subjective in Political Economy Communication Conflict within Legislature and Aceh Government - Zulham; Khairina AR.; Jummaini; Ristati (CV. Literasi Indonesia, 2022)
Interest will make someone selective in responding to or living a message. People will only pay attention to stimuli that have to do with their interests. The executive and legislative interests are power. The problem raised is that the achievement of power can be achieved by establishing effective communication. Collapsed communication between the executive and the legislature tends to lead to conflicts in the economy and politics. Based on this phenomenon, the author raises the issue of the occurrence of political economy communication conflicts between the two regional institutions. This research was conducted in Aceh, the approach used was qualitative using objective-subjective barrier theory, conflict theory, communication, communication conflict, and political economy. This study aims to determine the problems that arise in the political economy conflict. This research was conducted using observation and interview techniques. Furthermore, the data were analyzed descriptively. The results of this study are: prejudice is a factor in communication conflict. The lack of transparency and the governor's reluctance to sit down with members of the Aceh legislature to discuss regional and financial policies are considered by the council as a strategy by the governor to take advantage of the unilateral use of the budget.